Regulation of cardiac cAMP synthesis and contractility by nucleoside diphosphate kinase B/G protein βγ dimer complexes - Hippe, Hans-Jörg; Luedde, Mark; Lutz, Susanne; Koehler, Henrike; Eschenhagen, Thomas; Frey, Norbert; Katus, Hugo; Wieland, Thomas; Niroomand, Feraydoon (Circulation research, 2007)
Heterotrimeric G proteins are pivotal regulators of myocardial contractility. In addition to the receptor-induced GDP/GTP exchange, G protein α subunits can be activated by a phosphate transfer via a plasma membrane-associated complex of nucleoside diphosphate kinase B (NDPK B) and G protein βγ-dimers (Gβγ). To investigate the physiological role of this phosphate transfer in cardiomyocytes, we generated a Gβ1γ2-dimer carrying a single amino acid exchange at the intermediately phosphorylated His-266 in the β1 subunit (Gβ1H266Lγ2). Recombinantly expressed Gβ1H266Lγ2 were integrated into heterotrimeric G proteins in rat cardiomyocytes but were deficient in intermediate Gβ phosphorylation. Compared with wild-type Gβ1γ2 (Gβ1WTγ2), overexpression of Gβ1H266Lγ2 suppressed basal cAMP formation up to 55%. A similar decrease in basal cAMP production occurred when the formation of NDPK B/Gβγ complexes was attenuated by siRNA-mediated NDPK B knockdown. In adult rat cardiomyocytes expressing Gβ1H266Lγ2, the basal contractility was suppressed by ≈50% which correlated to similarly reduced basal cAMP levels and reduced Ser16-phosphorylation of phospholamban. In the presence of the β-adrenoceptor agonist isoproterenol, the total cAMP formation and contractility were significantly lower in Gβ1H266Lγ2 than in Gβ1WTγ2 expressing cardiomyocytes. However, the relative isoproterenol-induced increased was not affected by Gβ1H266Lγ2. We conclude that the receptor-independent activation of G proteins via NDPK B/Gβγ complexes requires the intermediate phosphorylation of G protein β subunits at His-266. Our results highlight the histidine kinase activity of NDPK B for Gβ and demonstrate its contribution to the receptor-independent regulation of cAMP synthesis and contractility in intact cardiomyocytes.